The value of eosinophil VCS parameters in predicting hepatotoxicity of antituberculosis drugs. (20th June 2016) - Shen, T.; Gu, D.; Zhu, Y.; Shi, J.; Xu, D.; Cao, X.
Summary: Introduction: Drug‐induced liver injury (DILI) is the most frequent cause of discontinuation of antituberculosis medication and difficult to predict. In recent years, liver eosinophilia has been associated with incidence of DILI. We hypothesize that morphologic changes in reactive eosinophils associated with DILI may be determined by LH750 (Beckman Coulter, Fullerton, CA) with VCS technology. Methods: The absolute eosinophil (AEC), percentage of eosinophil (EOSI%), VCS parameters, and standard deviation (SD) of 500 health controls, 376 patients without DILI, and 50 DILI patients were compared in terms of diagnostic sensitivity and specificity for DILI. Results: In DILI patients, the increased mean eosinophil volume (MEV) and size variability (MEV‐SD) were observed prior to alanine aminotransferase (ALT) elevations. The MEV was correlated well with ALT after therapy. The ROC curve analyses revealed that the MEV and MEV‐SD had larger areas under curves (0.894, 0.815, in the week prior to DILI) compared to other parameters. Using a cutoff of 163.15 fL for the MEV and a cutoff of 17.11 for MEV‐SD, the sensitivities of 81% and 72% and specificities of 82% and 80% were achieved, respectively, which are higher than other parameters prior to DILI occurred. Conclusions: The MEV with size variability (MEV‐SD) is a quantitative, objective, and more sensitive parameter and has a potential to be an additional indicator for DILI.